Simulation Model of System Enabled to Serve n Types of Messages - Gedmantas, R.; Jarutis, A.; Jarutis, J. (Elektronika ir Elektrotechnika, 2007)
Analysis of value added complementary services pose a specific problem, because distinct servicing algorithms have to be taken into account, while generating messages with different service times. This problem can be solved using analytical or simulation methods. Analytical models are not suited to evaluate specific details of the system being modeled, because of their complexity therefore simulation model of the system servicing different types of messages with different service times is presented in this paper. Sample size needed for desired accuracy is calculated. Results obtained with simulation are tested with Kolmogorov-Smirnov test against results obtained using steady state distribution of corresponding Markov chain. Ill. 8, bibl. 6 (in English; summaries in English, Russian, Lithuanian).